Evaluation of genetic relatedness among shorea parvifolia dyer parvfolia adult trees and saplings using rapd-pcr - Chong., Johnson (Universiti Malaysia Sarawak (UNIMAS), 2006)
The genetic relatedness among Shorea parvi(olia Dyer parvi(olia at Semengoh Forest Reserve, Sarawak was evaluated using randomly amplified polymorphic DNA (RAPD) analysis. Four arbitrary primers that produced informative, scorable and reproducible DNA bands were selected for evaluation of genetic relatedness among the adult trees. The cluster analysis of RAPD data using unweighted pair-group method with arithmetic averages (UPGMA) grouped the 8 adult trees into 3 clusters. The result revealed that four adult trees of S. parvi(olia Dyer parvi(olia were not closely related and therefore selected as potential mother trees for seed production. The RAPD was used to check for misidentified in the samples as well and one sample was misidentified. For evaluation of genetic relatedness among saplings and adult trees, cluster analysis of RAPD data using UPGMA grouped the 31 samples into 3 clusters. Out of 25 saplings, only 7 saplings closely related to the selected adult trees. These results were essential in the establishment of forest Seed Production Area (SPA) and demonstrated the usefulness of RAPD marker in detecting the wrongly identified samples.